2022
DOI: 10.3389/fpsyg.2022.859478
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Distress in Oncological Patients: The Revised Version of the Psychological Distress Inventory (PDI-R)

Abstract: BackgroundPsychological research in oncological settings is steadily increasing and the construct of psychological distress has rapidly gained popularity—leading to the development of questionnaires aimed at its measurement. The Psychological Distress Inventory (PDI) is one of the most used instruments, but its psychometric properties were not yet deeply evaluated. The present studies aimed at investigating the psychometric properties of the PDI (Study 1) and providing a revised version of the tool (Study 2).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…In order to reach this objective, a psychometric network analysis approach was used. The results of this study conducted with 3,009 participants confirmed that etiological beliefs are characterized by two poles—psychosocial and biological–genetic—and that these two poles are highly interconnected (e.g., Mannarini & Boffo, 2013; Rossi, Marconi, et al, 2022). Specifically, the thickest edge resulted between Item 6 (biological–genetic pole: “Some people have been depressed from birth and they will be depressed for the rest of their lives”) and Item 28 (psychosocial pole: “Childhood traumas, such as sexual abuse in a very violent family environment, might impede a healthy mental development”).…”
Section: Discussionsupporting
confidence: 61%
“…In order to reach this objective, a psychometric network analysis approach was used. The results of this study conducted with 3,009 participants confirmed that etiological beliefs are characterized by two poles—psychosocial and biological–genetic—and that these two poles are highly interconnected (e.g., Mannarini & Boffo, 2013; Rossi, Marconi, et al, 2022). Specifically, the thickest edge resulted between Item 6 (biological–genetic pole: “Some people have been depressed from birth and they will be depressed for the rest of their lives”) and Item 28 (psychosocial pole: “Childhood traumas, such as sexual abuse in a very violent family environment, might impede a healthy mental development”).…”
Section: Discussionsupporting
confidence: 61%
“…Preliminary analyses were performed: examination of items’ normality, the presence of excessive correlations (e.g., r > 0.85) among them [ 34 , 39 ] as well as their level of informativeness—an item may be deemed poorly informative if its standard deviation (SD) falls 2.5 standard deviations below the mean of all items [ 40 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Articles by the developers of semiparametric norming (A. Lenhard et al, 2018a) reported the most detailed information; other authors described their models as supplements (Echemendia et al, 2021) or did not report clear information on the model (Rossi et al, 2022).…”
Section: Continuous Norming Methodsmentioning
confidence: 99%